PENGARUH KESEDIAAN BERBAGI PENGETAHUAN PADA SIKAP DALAM BEKERJA TIM - Dinda Amalia; Hajan Hidayat (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
This study aims to determine the influence of willingness to share knowledge of attitudes in team work. In the measurement of attitude in team work, this study uses two dimensions that is perceptions of team performance effectiveness and student interest in team work. The research method used a quantitative method approach. This study uses primary data. The instrument method is Likert scale. Sampling research using purposive sampling method. The author set the number of samples to be studied at least 200 samples with the category of students who are in accounting majors. The results of this study indicate that the willingness to share knowledge affect the perceptions of the effectiveness of team work and willingness to share knowledge affect the student's interest in team work. Future research is expected to add a wider sample and can add an assessment dimension to the knowledge sharing willingness variable. This research can be used as consideration or as a reference and additional information for researchers who will conduct further research on team work.